Been, being, becoming: an auto-ethnographical analysis of black youth in Canada - Odera, James (My University, 2020)
Black youth often contend with negative external social constructions, labels, and categories, defining who they are as individuals and as racialized others. Regardless of the degree to which Black youth identify with these narratives of deviance, the expectations and assumptions within this discourse have consequences. This research project analyzed Black youth identity and racialization through the lens of my racialized experience of growing up Black in Canada. Thus, this study attempted to answer the following question: How have I as a Black youth made sense of the “narrative of deviance” as I created my identity during adolescence? The method used for this research was an auto-ethnographical approach, which allowed me to analyze my own life experiences and explore the themes in relation to academic literature on Black youth and adolescent experiences. As the primary researcher I coded the selected life experiences using MAXQDA coding software, analyzed them for major themes, and drew on the major connections that existed between the data and the existing literature. The existing literature represented Black youth identity as frequently being fraught with internal identity tension, varying levels of performative tendencies, and denial of individual recognition. My research found that throughout my life, I contended with social process that constructed Blackness, through creation, performance, and judgment, making my Blackness an object that was meant to represent a stereotypical image of a Black male.
Presented in absentia on April 27, 2020 at "Student Research Day" at MacEwan University in Edmonton, Alberta. (Conference cancelled)
Keywords: Blackness; youth; identity; performance; auto-ethnography